The role of Women and Children Protection Technical Implementation Units in alleviating child abuses during the Covid-19 pandemic - Chesa Syaqira Makmur; Septiana Dwiputri Maharani; Budi Andayani (Jurnal Sosiologi Dialektika, 2022)
Child protection is the most important part of protecting the nation’s generation from the dangers of crime in society. It is happened due to the fact that childhood is vulnerable to violence and abuse. Children’s behavior and life have changed as a result of the Covid-19 pandemic. The current study aims to analyze the scope of duties and functions of UPT PPA (the Women and Children Protection Technical Implementation Units) in alleviating the child abuse cases in Yogyakarta, especially during the Covid-19 Pandemic. The current study employed a qualitative method. The data were collected by observation from the related parties and interviews. This study resulted in the findings that UPT PPA Yogyakarta City assisted in the recovery process for victims of violence through early prevention of violence, assistance, and social reintegration. This study concludes that the efforts made by the UPT PPA of Yogyakarta City have helped to increase family resilience after the occurrence of violence.